PERCEPTIONS OF FOREIGN LANGUAGE TEACHERS ON FOREIGN LANGUAGE TEACHING DURING THE CORONAVIRUS PANDEMIC - Kazu, İbrahim Yaşar; Yalçin, Cemre Kurtoğlu; Yalçin, Cemal (T.C. Milli Egitim Bakanligi, 2022)
The aim of this study is to determine the problems that foreign language teachers encounter during the foreign language education process through distance education during the pandemic period and their solutions. A total of 92 foreign language teachers from different schools in Elazig, Turkey were enrolled in the study which was conducted in 2020-2021 academic year. The data were obtained through a semi-structured interview form called ‘Opinions of Foreign Language Teachers Regarding Foreign Language Teaching Performed by Distance Education in the Covid-19 Pandemic Process’, which was prepared as an online data collection tool via Google form, consisting of open-ended questions. A phenomenology method which is a qualitative research method was used. Data were analyzed by using content analysis. As a result of the study, it was understood that teachers had problems due to technical reasons such as disconnection, not being able to connect due to systemic intensity, and sound problems while connecting to lessons. In addition, in the dimension of foreign language education, problems such as the difficulty of gaining foreign language skills through distance education and not getting the expected level of feedback from students were mentioned. Teachers suggested increasing the number of foreign language lessons and developing materials for distance education. © 2022. Milli Egitim.All Rights Reserved
YABANCI DİL ÖĞRETMENLERİNİN GÖZÜNDEN PANDEMİ DÖNEMİNDE YABANCI DİL ÖĞRETİMİ
Keywords: Covid-19; Distance education; Epidemic; Foreign language education; Foreign language teachers; Pandemic